Dynamics and Administrative Behavior of a Multi-Disciplinary Medical Center - Engelbrecht, R.; Schmeetz, H.-D.; Laude, G.; Gaertner, H.-O. von; Reichertz, P. L. (Methods of Information in Medicine, 1976)
The organizational structure of the Medical School Hannover is described. Information flow connects the different clinical structures. Existing EDP-based systems, the functional characteristics of which are described, are able to determine part of this flow. Characteristic parameters are found from the measurements for single organizational units. These parameters allow first descriptions of the system. They also provide an entry point for a possible steering and tuning of the system. First results of such an intervention are discussed.
Keywords: Hospital Information System; Administrative Sector; Patient Admission System; Budget System; Inventory Information System; Personnel Information System; Drug Usage Control